Karakterisasi Konveks Melalui Pertidaksamaan Matriks Non Linier pada Analisis Stabilitas Kendali Hâˆž untuk Sistem Non Linier - Asep Najmurrokhman (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2002)
In this paper, stability analysis of nonlinear systems is considered. Existence of Lyapunov function as stability guarantee for a class of nonlinear systems is characterized in terms of nonlinear matrix inequalities which result in convex feasibility problems. A numerical example will be shown for clarity this method. The issue of solutions to these nonlinear matrix inequalities is proposed.